Cold atmospheric plasma induces apoptosis in human colon and lung cancer cells through modulating mitochondrial pathway - Wang, Yanhong; Mang, Xinyu; Li, Xuran; Cai, Zhengyu; Tan, Fei (Frontiers in Cell and Developmental Biology, 2022)
Cold atmospheric plasma (CAP) is an emerging and promising oncotherapy with considerable potential and advantages that traditional treatment modalities lack. The objective of this study was to investigate the effect and mechanism of plasma-inhibited proliferation and plasma-induced apoptosis on human lung cancer and colon cancer cells in vitro and in vivo. Piezobrush® PZ2, a handheld CAP unit based on the piezoelectric direct discharge technology, was used to generate and deliver non-thermal plasma. Firstly, CAPPZ2 treatment inhibited the proliferation of HT29 colorectal cancer cells and A549 lung cancer cells using CCK8 assay, caused morphological changes at the cellular and subcellular levels using transmission electron microscopy, and suppressed both types of tumor cell migration and invasion using the Transwell migration and Matrigel invasion assay. Secondly, we confirmed plasma-induced apoptosis in the HT29 and A549 cells using the AO/EB staining coupled with flow cytometry, and verified the production of apoptosis-related proteins, such as cytochrome c, PARP, cleaved caspase-3 and caspase-9, Bcl-2 and Bax, using western blotting. Finally, the aforementioned in vitro results were tested in vivo using cell-derived xenograft mouse models, and the anticancer effect was confirmed and attributed to CAP-mediated apoptosis. The immunohistochemical analysis revealed that the expression of cleaved caspase-9, caspase-3, PARP and Bax were upregulated whereas that of Bcl-2 downregulated after CAP treatment. These findings collectively suggest that the activation of the mitochondrial pathway is involved during CAPPZ2-induced apoptosis of human colon and lung cancer cells in vitro and in vivo.